PENEGAKAN HUKUM TINDAK PIDANA PERTAMBANGAN PASIR ILLEGAL (STUDI KASUS DI KELURAHAN NAMBO KOTA KENDARI SULAWESI TENGGARA) - Yulian Yusuf, Niken; Kurnaiwati, Wa Ode Intan; Supriadi, Supriadi; Yusuf, M.; Ismail, La Ode; Basri, Muhammad; Tamar Yakub, L.M Yakda (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2024)
This study aims to determine and analyze the factors that cause Illegal sand mining in Nambo Village, Kendari City and to understand and analyze the law enforcement of illegal sand mining in Nambo Village, Kendari City, Southeast Sulawesi. Literature research method. The result of the research is that the problem of illegal sand mining is caused by various complex factors, ranging from high demand for sand, weak law enforcement, to lack of public awareness and economic alternatives. Effective handling requires comprehensive efforts from various parties, including the government, law enforcement officials, academics, and the community. Enforcement of illegal sand mining is carried out by controlling mining points that do not have licenses. It was observed that people's sand mining was also still closed, triggering community protests. In addition, heavy equipment confiscation and the determination of suspects for illegal mining perpetrators were also carried out. However, this needs to be balanced with the ease of community mining permits and assistance for the community in carrying out mining activities.